Robert S. Wagman, The Cave of the Nymphs at Pharsalus. Studies on a Thessalian Country Shrine - Mili, Maria (Journal of Greek Archaeology, 2021)
The book is a welcome addition to recent works on the cults of the area of Thessaly in anglophone scholarship. Of the various sanctuaries excavated in Thessaly, we have very few systematic studies of sanctuary material. Beyond the Thessalian confines, this book is an important contribution to the topics of Nymph cults and nympholepsy, Greek sanctuaries and their natural environment and indeed cave cults.